Development and Validation of RP-HPLC Analysis Method for Determination of Total Alkaloid Content of Soursop (Annona muricata L.) Leaf Extract - Lindawati Setyaningrum; Dyah Purwaningtyas; Ayik Rosita Puspaningtyas; Dyan Wigati; Mohammad Rofik Usman; Maasyitoh Sari Latifah (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2022)
Soursop leaves contain alkaloids that have pharmacological effects. This study aims determine the total alkaloid content of soursop leaf ethanol extract using a validated HPLC method. Extraction was carried out by soxhletation followed by liquid-liquid extraction using chloroform. Optimizing HPLC conditions on the mobile phase, flow rate, concentration, and wavelength, further testing the validation of the analytical method. Optimizing HPLC conditions obtained optimal results at concentration of 500 ppm with a flow rate of 1.0 mL/min using acetonitrile: methanol: water (80:5:15) at wavelength of 272 nm. These results have met the validation requirements of analytical methods including System Suitability Test (UKS), selectivity, linearity with y = 2.01914x –219,97226, correlation coefficient value (r) = 0.9995, and Vx0 value 0.11201%. The limit of detection and quantization were 8,78525 ppm and 29,28418 ppm, respectively. The RSD percentage of the precision test is 1.0453%, and the accuracy test is obtained from the recovery of 98-102%. The result of determining the total alkaloid content sample was 0.0862 ± 0.004 % (%w/w) of the entire alkaloid content (TALC) triple replication. This research concludes that the analytical method using the HPLC system for determining the total alkaloid content of the ethanolic extract of soursop leaves is validate